2016
DOI: 10.1103/physreva.93.023821
|View full text |Cite
|
Sign up to set email alerts
|

Beyond mean-field bistability in driven-dissipative lattices: Bunching-antibunching transition and quantum simulation

Abstract: In the present work we investigate the existence of multiple nonequilibrium steady states in a coherently-driven XY lattice of dissipative two-level systems. A commonly-used mean-field ansatz, in which spatial correlations are neglected, predicts a bistable behavior with a sharp shift between low-and high-density states. In contrast one-dimensional matrix product methods reveal these effects to be artifacts of the mean-field approach, with both disappearing once correlations are taken fully into account. Inste… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
89
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(90 citation statements)
references
References 85 publications
1
89
0
Order By: Relevance
“…In this section, we investigate the driven-dissipative spin-1/2 XYM in (4). In particular, we study the antibunching-bunching transition of the nearest neighbor correlator as a function of the detuning Δ, which was recently predicted in [52] using large scale MPS simulations. In the following, we (i) provide a simple and analytic explanation of the transition based on a minimal model of two coupled spins (dimer), (ii) reproduce exact numerical results with the self-consistent z 1 method to high accuracy and (iii) go beyond the MPS method by also studying the 2D case.…”
Section: Spin-1/2 Xy Model: Antibunching-bunching Transitionmentioning
confidence: 99%
“…In this section, we investigate the driven-dissipative spin-1/2 XYM in (4). In particular, we study the antibunching-bunching transition of the nearest neighbor correlator as a function of the detuning Δ, which was recently predicted in [52] using large scale MPS simulations. In the following, we (i) provide a simple and analytic explanation of the transition based on a minimal model of two coupled spins (dimer), (ii) reproduce exact numerical results with the self-consistent z 1 method to high accuracy and (iii) go beyond the MPS method by also studying the 2D case.…”
Section: Spin-1/2 Xy Model: Antibunching-bunching Transitionmentioning
confidence: 99%
“…A recent work [73] showed that collective bistability in the driven-dissipative XY spin-1 2 model vanishes as the Gutzwiller approximation is systematically improved. Our results demonstrate that whileρ ss is indeed unique [74,75], it retains clear signatures of the MF bistability, namely that the system dynamically switches between two macroscopically distinguishable configurations that resemble the MF steady statesρ 1 andρ 2 ; in fact, this is a generic feature of bistable systems [60,61,65,76,77].…”
Section: Collective Bistability and Switchingmentioning
confidence: 99%
“…There have been several recent proposals [8][9][10][11][12] on achieving this model with photons and open systems, such as with photons in coupled cavity arrays, superconducting circuit QED and polaritons. With added drive and dissipation, the Bose-Hubbard model does not exhibit superfluid or Mott insulator phases but gives rise to mixed state nonequilibrium steady states and phases [13][14][15][16], the nature and generation of which are not fully understood.…”
Section: Introductionmentioning
confidence: 99%